1991
DOI: 10.1073/pnas.88.9.3720
|View full text |Cite
|
Sign up to set email alerts
|

Cross-family dimerization of transcription factors Fos/Jun and ATF/CREB alters DNA binding specificity.

Abstract: The Fos/Jun and ATF/CREB families of transcription factors function in coupling extracellular signals to alterations in expression of specific target genes. Like many eukaryotic transcription factors, these proteins bind to DNA as dimers. Dimerization is mediated by a structure known as the "leucine-zipper" motif. Although Fos/Jun and ATF/CREB were previously thought to interact preferentially with different DNA regulatory elements (the AP-1/TRE and ATF/CRE sites, respectively), we rind that members of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
677
1
6

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,184 publications
(697 citation statements)
references
References 45 publications
13
677
1
6
Order By: Relevance
“…This phosphorylation is thought to alter the conformation of the transactivation domain which presents the glutamine rich regions for interaction with the pre-initiation complex [51]. CREB is able to dimerize with CREM or ATF-1, but there is also possible heterodimerization of ATF members with c-fos, c-jun or C/EBP [29,52]. It has been shown that CREB could act synergistically with nuclear receptors such as SF-1 [53].…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorylation is thought to alter the conformation of the transactivation domain which presents the glutamine rich regions for interaction with the pre-initiation complex [51]. CREB is able to dimerize with CREM or ATF-1, but there is also possible heterodimerization of ATF members with c-fos, c-jun or C/EBP [29,52]. It has been shown that CREB could act synergistically with nuclear receptors such as SF-1 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Activator protein-1 (AP-1) is a dimeric transcription factor composed of members of the Jun family (c-Jun, JunB and JunD), which form homodimers or heterodimers with members of the Fos family (c-Fos, Fra-1, Fra-2 and FosB) and activating transcription factor (ATF) proteins (Hai and Curran, 1991). AP-1 modulates transcription by binding to TPA-response element (TRE) or cAMP-response element (CRE) consensus elements and is involved in proliferation, differentiation and apoptosis (Lee et al, 1987;Halazonetis et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…ATF-2 can form either homodimers or heterodimers with c-Jun: the dimers subsequently bind to the cyclic AMP response element (CRE: 5Ј-TGACGTCA-3Ј) and positively regulate transcription (Hai and Curran, 1991). Stress-activated protein kinases (SAPKs) such as p38 and JNK (c-Jun N-terminal protein kinase) phosphorylate ATF-2 at Thr-69 and Thr-71 close to the N-terminal transcriptional activation domain containing the zinc finger domain and thereby enhance its trans-activating capacity (Gupta et al, 1995;Livingstone et al, 1995;van Dam et al, 1995).…”
Section: Introductionmentioning
confidence: 99%